Tradition of Tafsir in Urdu Language - Zaman, Shazia; Hashmi, Munawar; Liaqat, Muhammad (sourcecoder, 2023)
The term "Tafsir" is an Arabic word, meaning to clarify something, like to express any expression with clarification. The science of explaining the knowledge of the Holy Quran with clarity is called "Tafsir," and the one who explains it is called an "exegete" and the plural of Tafsir is Tafasir. Abdur al-Rahman ibn Abi Bakr's Tafsir is mentioned in the following manner: "Tafsir means the knowledge by which the Quranic revelations sent down to the Noble Prophet (Peace Be upon Him) are understood, and its rulings, issues, and secrets are discussed." The fundamental purpose of the descent of the Quran is success and prosperity for all human beings in both worlds. Learning the translation and interpretation of the Quran is essential for all human beings. This is why the importance of Tafsir has remained significant in every era so that people can understand the Divine Word and lead successful lives. Tafsir comprehensively explains the chapters of the Holy Quran with coherence. It elaborates on the reasons for revelation and virtues in an organized manner. Studying the interpretation of the Quran is crucial for the Muslim community because Tafsir is a discipline that explains the explanation of the Holy Quran, and by understanding it, it becomes clear that the Quran is a source of success and guidance for all humanity. Tafsir is also necessary because the reader can learn the method of living life according to the commandments of Allah in ethics, transactions, and worship, and can achieve success in both his religious and worldly life.